The cannabinoids - important therapeutic approach in the field of oncology - Nicoleta Mirela Blebea; Laura Adriana Bucur; Simona Negreș (Amaltea Medical Publishing House, 2021)
Oncological diseases are the most common cause of death worldwide, it is estimated that 25% of the population will face the diagnosis of cancer during life. Phytochemicals such as cannabinoids (CBs) have been used in various branches of medicine for their properties, and the discovery of the anti-tumor, anti-emetic and anti-inflammatory effects of some of these substances has encouraged their use in oncology. Phytocannabinoids, cannabidiol (CBD) and Δ-9-tetra-hydrocannabinol (THC), have numerous anti-emetic, analgesic, orexigenic, anti-inflammatory / immunosuppressive pharmacodynamic effects. In recent years, studies have been aimed at evaluating their efficacy as antineoplastic agents. Much in vivo and in vitro research has demonstrated the efficacy of CBs on certain tumor cell lines, highlighting their potential role in the complementary treatment of cancer. This paper suggests that exploring the molecular mechanisms induced by CBs in cancer cells may contribute to the development of effective treatments in oncological diseases.